Prevalence of non-communicable disease risk factors in three sites across Papua New Guinea: a cross-sectional study. Issue 2 (14th June 2017) - Rarau, Patricia; Vengiau, Gwendalyn; Gouda, Hebe; Phuanukoonon, Suparat; Kevau, Isi H; Bullen, Chris; Scragg, Robert; Riley, Ian; Marks, Geoffrey; Umezaki, Masahiro; Morita, Ayako; Oldenburg, Brian; et al.
Abstract : Papua New Guinea (PNG) is a culturally, environmentally and ethnically diverse country of 7.3 million people experiencing rapid economic development and social change. Such development is typically associated with an increase in non-communicable disease (NCD) risk factors. Aim: To establish the prevalence of NCD risk factors in three different regions across PNG in order to guide appropriate prevention and control measures. Methods: A cross-sectional survey was undertaken with randomly selected adults (15–65 years), stratified by age and sex recruited from the general population of integrated Health and Demographic Surveillance Sites in West Hiri (periurban), Asaro (rural highland) and Karkar Island (rural island), PNG. A modified WHO STEPS risk factor survey was administered along with anthropometric and biochemical measures on study participants. Results: The prevalence of NCD risk factors was markedly different across the three sites. For example, the prevalences of current alcohol consumption at 43% (95% CI 35 to 52), stress at 46% (95% CI 40 to 52), obesity at 22% (95% CI 18 to 28), hypertension at 22% (95% CI 17 to 28), elevated levels of cholesterol at 24% (95% CI 19 to 29) and haemoglobin A1c at 34% (95% CI 29 to 41) were highest in West Hiri relative to the rural areas. However, central obesity at 90% (95% CI 86 to 93) and prehypertension at 55% (95% CI 42 to 62) were most common in Asaro whereas prevalences of smoking, physical inactivity and low high-density lipoprotein-cholesterol levels at 52% (95% CI 45 to 59), 34% (95% CI 26 to 42) and 62% (95% CI 56 to 68), respectively, were highest in Karkar Island. Conclusion: Adult residents in the three different communities are at high risk of developing NCDs, especially the West Hiri periurban population. There is an urgent need for appropriate multisectoral preventive interventions and improved health services. Improved monitoring and control of NCD risk factors is also needed in all regions across PNG.